2020
DOI: 10.1016/j.jid.2019.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor RNA Activator, a Long Noncoding RNA, Activates p38, Facilitates Epithelial-Mesenchymal Transformation, and Mediates Experimental Melanoma Metastasis

Abstract: Melanoma metastasis signals dismal prognosis even with current checkpoint inhibitors. Long noncoding RNAs (lncRNAs) regulate dynamic metastasis in several cancers, including melanoma. We became interested in a lncRNA, steroid receptor RNA activator (SRA), because it is the first lncRNA also encoding a conserved protein, SRAP, and it regulates progression of prostate and breast cancers. We investigated how SRA mediates melanoma proliferation, migration, invasion, epithelial-mesenchymal transformation (EMT), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…We attempted to identify the common pathways that are involved in both melanogenesis or carcinogenesis and SRA signaling. The literatures search revealed that p38 MAPK [ 14 , 21 ] and Notch-1 [ 20 , 22 ] are indeed involved in both pathophysiological processes. Hence, we measured the activation of p38 and the cleavage of Notch1 by western blotting after inhibiting SRA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attempted to identify the common pathways that are involved in both melanogenesis or carcinogenesis and SRA signaling. The literatures search revealed that p38 MAPK [ 14 , 21 ] and Notch-1 [ 20 , 22 ] are indeed involved in both pathophysiological processes. Hence, we measured the activation of p38 and the cleavage of Notch1 by western blotting after inhibiting SRA.…”
Section: Resultsmentioning
confidence: 99%
“…We attempted to identify the common pathways that are involved in both melanogenesis or carcinogenesis and SRA signaling. The literatures search revealed that p38 MAPK [14,21] and Notch-1 [20,22] are indeed involved in both https://doi.org/10.1371/journal.pone.0237577.g002…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of SRA could significantly reduce melanoma development, which was mediated by p38 activation. 41 The therapy of melanoma is still pool, these studies provided new ways to improve the prognosis of melanoma.…”
Section: Melanoma and Squamous Cell Carcinomasmentioning
confidence: 99%
“…Current knowledge about lncRNAs shows that they are involved in the pathogenesis of various diseases, particular for cancers [8,9]. In melanoma, several lncRNAs were recently reported to be associated with the initiation and progression of melanoma, such as SPRY4-IT1, Llme23, OVAAL, SRA, and LINC00520 [10][11][12][13][14]. In our previous reports, we also identified three oncogenic lncRNAs in melanoma: PVT1, ILF3-AS1, and MHENCR [15][16][17].…”
Section: Introductionmentioning
confidence: 97%